Due Process of Law : Personal Data Legal Certainty (SIM Card Criminal Acts) (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The purpose of this research is to investigate the misuse of personal information and data on SIM cards, which has raised significant concerns regarding the security of personal data and potential cyber violations, particularly in relation to law enforcement, especially after the enforcement of Law Number 27 of 2022 regarding the Protection of Personal Data. The increasing prevalence of data misuse and cybercrimes, particularly those involving SIM card registration, has become a major issue that needs urgent attention, as it directly affects citizens' privacy and security. This study adopts an empirical legal method, incorporating statute, conceptual, and case approaches within a descriptive-qualitative framework. The research findings indicate that criminal acts occur during the prepaid SIM card registration process, which requires the personal information of the subject, along with their written or recorded consent. The illegal usage of personal data on SIM cards, as if it were the subject’s own, constitutes a violation of the law, and this practice is being increasingly observed. The implementation of Due Process of Law ensures legal certainty, as evidenced in the Salatiga District Court case No. 46/Pid.Sus/2023/PN.Slt, where the case highlighted the lack of accountability and enforcement in such instances. However, the study highlights the need for further harmonization of existing regulations, increased public awareness, stricter penalties, and improved implementation of police reports using Model A and Model B. This research emphasizes the importance of developing stronger legal measures to address the misuse of personal data, protect citizens’ privacy, and uphold the integrity of the law in the digital age. The findings underscore the critical role of both legislation and law enforcement in ensuring the protection of personal data and safeguarding the rights of individuals in the face of evolving digital threats.